Proper Determination of Tunnel Model Parameters for Indirect Band-to-Band Tunneling in Compressively Strained Si1-xGex TFETs - Nguyễn, Đăng Chiến (IEEE Publishing, 2024)
Tunnel field-effect transistor (TFET) has served as one of the most attractive candidates for use in future low-power integrated circuits. To explore the current-voltage characteristics of TFET devices, the Kane’s tunnel model has been widely used in numerical simulations and physical models to predict the tunneling current produced in the TFETs. This study examines the proper calculations of Kane’s model parameters appropriate for the indirect band-to-band tunneling generated in compressively strained Si1-xGex channel on Si-substrate. The calculated parameters were verified with the measured results from experimental TFETs. Good agreements are confirmed between the numerical and measured data without any fitting factors.